Preparation method of porous carbon loaded nano nickel applied to hydrogen evolution catalyst

By preparing porous carbon-supported nano nickel, the problem of low activity in electrochemical hydrogen evolution and easy agglomeration of nickel-based catalysts is solved, and efficient electrochemical hydrogen evolution activity and corrosion resistance are achieved.

CN119710779APending Publication Date: 2025-03-28NANTONG JUNXI METAL PRODUCTS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510181446.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-19
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Traditional porous carbon catalysts are not very active in electrochemical hydrogen evolution, nickel-based catalysts are prone to agglomeration, and the active sites are not exposed sufficiently.

Method used

By preparing porous carbon-supported nanonier, using benzotriazole, dimethyl 2,5-dibromodipate, acid binder potassium carbonate, phase transfer catalyst polyethylene glycol 400, and hydrazine hydrate as raw materials, bisbenzotriazole bishydrazole compound was prepared, and reacted with 2,3-dihydroxy terephthalaldehyde to Schiff base, cross-link polymerization to produce a microporous polymer containing catechol and benzotriazole structural units. Nickel ions are supported in the microporous polymer, and porous carbon-supported nanonier is formed by high-temperature annealing.

Benefits of technology

The electrochemical hydrogen evolution activity is improved, the agglomeration and corrosion problems of nickel catalysts are avoided, and the conductive properties and catalytic activity of the catalysts are enhanced. The hydrogen evolution overpotential is -0.208 to -0.089V, and the Taffier slope is 69-98mV/dec.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119710779A_ABST
    Figure CN119710779A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of electrochemical energy, and discloses a preparation method of porous carbon-loaded nano nickel applied to a hydrogen evolution catalyst, the porous carbon-loaded nano nickel is used as an electrochemical hydrogen evolution catalyst, the agglomeration phenomenon of nickel nanoparticles is improved, the problem of insufficient exposure of active catalytic sites is solved, and the electrochemical hydrogen evolution catalyst has good electrochemical performance. In addition, after the nickel nanoparticles are loaded by the porous carbon, the problem that the catalyst is corroded by electrolyte is solved; the nitrogen-doped porous carbon has better conductivity and catalytic activity, can promote electron migration in an electrochemical hydrogen evolution reaction, and further enhances the hydrogen evolution activity of the catalyst; the hydrogen evolution overpotential ranges from-0.208 V to-0.089 V, and the Tafel slope ranges from 69 mV / dec to 98 mV / dec.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of electrochemical energy, in particular to a method for preparing porous carbon-loaded nano-nickel used in hydrogen evolution catalysts. Background Art

[0002] The two major problems facing the development of human society today are energy crisis and environmental pollution. Hydrogen is a clean energy with high energy density and green environmental protection, which has great prospects in solving energy crisis and environmental pollution problems. How to produce hydrogen efficiently and controllably is of great significance. Electrolysis of water to produce hydrogen is an electrochemical hydrogen evolution method with great development potential and has been widely studied by scientific researchers. The development of low-cost and efficient HER hydrogen evolution catalysts is the key to promoting and applying hydrogen energy.

[0003] Porous carbon materials have excellent electrical conductivity, high specific surface area, and good catalytic performance, and are widely used in energy storage, catalyst carriers, gas storage and other fields; the patent with announcement number CN113136591B discloses the use of ethylenediaminetetraacetate as a ligand and carbon source, combined with ruthenium salt to prepare a ruthenium complex precursor, which is then pyrolyzed at high temperature to obtain ruthenium and nitrogen co-doped porous carbon, which can be used in electrolytic hydrogen evolution; however, catalysts such as ruthenium and platinum are precious metals and are difficult to develop and apply on a large scale commercially.

[0004] Although transition metal elements nickel, iron, molybdenum and their oxides have good catalytic properties, these catalysts are easily corroded by the electrolyte in reactions such as electrochemical hydrogen evolution, and have disadvantages such as easy agglomeration and insufficient exposure of active sites. Loading active catalysts such as nickel into porous carbon materials can effectively solve the above problems. Summary of the invention

[0005] The technical problem solved by the present invention is: a new porous carbon-supported nano-nickel is prepared and applied to hydrogen evolution catalysts to solve the problem that the hydrogen evolution activity of traditional porous carbon catalysts is not high, and the problem that nickel-based catalysts are easy to agglomerate and the active sites are not fully exposed.

[0006] The technical solution of the present invention is: a porous carbon-supported nano-nickel is prepared according to the following method: Step S1, introducing nitrogen into a three-necked flask, adding N,N-dimethylformamide solvent, 2,3-dihydroxyterephthalaldehyde, bisbenzotriazole dihydrazide compound and glacial acetic acid, cooling after reaction, filtering, washing with ethanol, and drying to obtain a microporous polymer containing catechol and benzotriazole structural units.

[0007] Step S2, adding N,N-dimethylformamide solvent and the above-mentioned microporous polymer to a flask, ultrasonically vibrating in an ultrasonic device for 30-60 min, then adding nickel nitrate and water, continuing ultrasonic vibration for 30-60 min, and then stirring for 12-24 h, controlling the stirring temperature to 25-50° C., filtering, washing with water, and drying to obtain a microporous polymer coordinated with nickel ions.

[0008] Step S3, the microporous polymer coordinated with nickel ions is placed in a tubular furnace, nitrogen is introduced, the temperature is increased to 700-900° C. at a heating rate of 2-5° C. / min, and annealed for 2-3 hours to obtain porous carbon-supported nano-nickel.

[0009] Furthermore, in step S1, the ratio of N,N-dimethylformamide solvent, 2,3-dihydroxyterephthalaldehyde, bisbenzotriazole dihydrazide compound and glacial acetic acid is (40-60) mL:1 g:(2.2-2.7) g:(4.5-6) ​​mL.

[0010] Furthermore, in step S1, the reaction temperature is controlled to be 100-130° C. and the reaction time is 48-96 h.

[0011] Furthermore, in step S2, the ratio of N,N-dimethylformamide solvent, microporous polymer, nickel nitrate and water is (20-80) mL:1 g:(1-6) g:(15-60) mL.

[0012] Furthermore, the bisbenzotriazole bishydrazide compound in step S1 is prepared according to the following method: Step S3, adding benzotriazole, dimethyl 2,5-dibromoadipate, polyethylene glycol 400, and potassium carbonate aqueous solution into a flask, performing ultrasound-assisted reaction in an ultrasonic device, cooling after the reaction, adding water to precipitate, filtering, washing with water, and drying to obtain an intermediate.

[0013] Step S4, adding methanol solvent, the intermediate and hydrazine hydrate to a flask, stirring the reaction for 3-10 h, controlling the reaction temperature to 30-40° C., and performing silica gel column chromatography after the reaction, using an eluent with a volume ratio of ethyl acetate:n-hexane = 1:10 to obtain a bisbenzotriazole bishydrazide compound.

[0014] Furthermore, in step S3, the ratio of benzotriazole, dimethyl 2,5-dibromoadipate, polyethylene glycol 400, and potassium carbonate aqueous solution is (0.7-0.9) g:1 g:(0.05-0.08) g:(5-15) mL.

[0015] Furthermore, the mass fraction of the potassium carbonate aqueous solution in step S3 is (0.12-0.6) g / mL.

[0016] Furthermore, in step S3, the frequency of the ultrasound-assisted reaction is 20 KHz, the reaction temperature is controlled to be 50-80° C., and the reaction time is 1-3 h.

[0017] Furthermore, in step S4, the ratio of methanol solvent, intermediate and hydrazine hydrate is (10-20) mL:1 g:(1.6-3) mL.

[0018] The technical effect of the present invention is as follows: the present invention uses benzotriazole, dimethyl 2,5-dibromoadipate, acid-binding agent potassium carbonate, phase transfer catalyst polyethylene glycol 400 and hydrazine hydrate as raw materials to react to obtain a bisbenzotriazole bishydrazide compound, and then carries out a Schiff base reaction with 2,3-dihydroxyterephthalaldehyde to obtain a microporous polymer containing catechol and benzotriazole structural units through cross-linking polymerization; the microporous polymer has the characteristics of a large number of pore structures and a high specific surface area.

[0019] Nickel nitrate is coordinated and chelated by the catechol and benzotriazole structures in the microporous polymer, and nickel ions are loaded into the microporous polymer skeleton. After high-temperature annealing, the microporous polymer is carbonized to form nitrogen-doped porous carbon with a high specific surface area. The nickel ions are catalytically reduced at high temperature to generate nickel nanoparticles in situ in the porous carbon matrix, thereby achieving the uniform loading of nickel nanoparticles into the porous carbon skeleton.

[0020] Porous carbon-loaded nano-nickel as an electrochemical hydrogen evolution catalyst improves the agglomeration phenomenon of nickel nanoparticles and solves the problem of insufficient exposure of active catalytic sites, thereby enhancing the electrochemical hydrogen evolution activity. After the nickel nanoparticles are loaded on porous carbon, the problem of catalyst corrosion by electrolyte is overcome; nitrogen-doped porous carbon has better conductivity and catalytic activity, which can promote the migration of electrons in the electrochemical hydrogen evolution reaction and further enhance the hydrogen evolution activity of the catalyst; the hydrogen evolution overpotential is -0.208 to -0.089V, and the Tafel slope is 69-98mV / dec. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 It is the infrared spectra of bisbenzotriazole bishydrazide compound ANC and microporous polymer PANC.

[0022] Figure 2 It is the scanning electron micrograph of microporous polymer PANC and porous carbon loaded nano-nickel CANC.

[0023] Figure 3 is the LSV polarization curve of electrochemical hydrogen evolution.

[0024] Figure 4 It is the Tafel plot of electrochemical hydrogen evolution. DETAILED DESCRIPTION

[0025] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0026] Example 1 Preparation of bisbenzotriazole bishydrazide compound ANC: 8.2 g of benzotriazole, 10 g of dimethyl 2,5-dibromoadipate, 0.6 g of polyethylene glycol 400, and 100 mL of a 0.35 g / mL potassium carbonate aqueous solution were added to a flask, and an ultrasonic-assisted reaction was carried out in an ultrasonic device for 1 h. The ultrasonic frequency was 20 KHz, and the reaction temperature was controlled at 70 °C. After the reaction, the mixture was cooled, water was added to precipitate, filtered, washed with water, and dried to obtain an intermediate.

[0027] Add 200 mL of methanol solvent, 15 g of the above intermediate and 32 mL of hydrazine hydrate to the flask, stir and react for 6 h, control the reaction temperature to 40 °C, and perform silica gel column chromatography after the reaction. The eluent is a solution with a volume ratio of ethyl acetate: n-hexane = 1:10 to obtain a bisbenzotriazole bishydrazide compound ANC. Reaction route:

[0028] Instructions attached Figure 1 The infrared spectrum of bisbenzotriazole bishydrazide compound shows that the wave number is 1692cm -1 It is the absorption peak of the hydrazide group C=O of the bisbenzotriazole bishydrazide compound, 1572cm -1 It is the absorption peak of triazole C=N, 1302cm -1 It is the absorption peak of the hydrazide group NN.

[0029] Preparation of microporous polymer PANC containing catechol and benzotriazole structural units: Nitrogen was introduced into a three-necked flask, and 360 mL of N,N-dimethylformamide solvent and 6 g of 2,3-dihydroxyterephthalaldehyde ( ), 16.2g of bisbenzotriazole bishydrazide compound and 30 mL of glacial acetic acid, stirred for 96 hours, controlled the reaction temperature at 120°C, cooled after the reaction, filtered, washed with ethanol, and dried to obtain a microporous polymer PANC containing catechol and benzotriazole structural units. Figure 1 The infrared spectrum of the microporous polymer PANC shows that at 1628 cm -1 It is the absorption peak of Schiff base C=N bond, 3492cm -1is the absorption peak of phenolic hydroxyl group, 1702cm -1 is the absorption peak of the hydrazide group C=O, 1522 cm -1 It is the absorption peak of triazole C=N.

[0030] Preparation of microporous polymer coordinated nickel ions: Add 100 mL of N,N-dimethylformamide solvent and 5 g of the above-mentioned microporous polymer into a flask, ultrasonically vibrate for 30 min in an ultrasonic device, then add 5 g of nickel nitrate and 75 mL of water, continue ultrasonic vibration for 60 min, then stir for 12 h, control the stirring temperature to 30 ° C, filter, wash with water, and dry to obtain a microporous polymer coordinated with nickel ions.

[0031] Preparation of porous carbon-supported nano-nickel CANC: The microporous polymer coordinated with nickel ions was placed in a tube furnace, nitrogen was introduced, the temperature was raised to 700°C at a heating rate of 2°C / min, and annealed for 3 hours to obtain porous carbon-supported nano-nickel CANC. Figure 2 The scanning electron microscope images of the mesoporous polymer PANC and the porous carbon-loaded nano-nickel CANC show that both the microporous polymer PANC and the porous carbon-loaded nano-nickel CANC have uniform and abundant microporous structures and have the advantage of large specific surface area.

[0032] Example 2 Preparation of bisbenzotriazole bishydrazide compounds: 7 g of benzotriazole, 10 g of dimethyl 2,5-dibromoadipate, 0.5 g of polyethylene glycol 400, and 50 mL of a 0.6 g / mL potassium carbonate aqueous solution were added to a flask, and an ultrasonic-assisted reaction was performed in an ultrasonic device for 1 h. The ultrasonic frequency was 20 KHz, and the reaction temperature was controlled to be 80 °C. After the reaction, the mixture was cooled, water was added to precipitate, filtered, washed with water, and dried to obtain an intermediate.

[0033] Add 300 mL of methanol solvent, 15 g of the intermediate and 45 mL of hydrazine hydrate to a flask, stir and react for 3 h, control the reaction temperature to 40 °C, and perform silica gel column chromatography after the reaction. The eluent is a solution with a volume ratio of ethyl acetate:n-hexane = 1:10 to obtain a bisbenzotriazole bishydrazide compound.

[0034] Preparation of microporous polymers containing catechol and benzotriazole structural units: Nitrogen was introduced into a three-necked flask, and 300 mL of N,N-dimethylformamide solvent, 6 g of 2,3-dihydroxyterephthalaldehyde, 14.5 g of bisbenzotriazole bishydrazide compound and 30 mL of glacial acetic acid were added. The reaction was stirred for 96 h, and the reaction temperature was controlled at 100°C. After the reaction, the mixture was cooled, filtered, washed with ethanol, and dried to obtain a microporous polymer containing catechol and benzotriazole structural units.

[0035] Preparation of microporous polymer coordinated nickel ions: Add 200 mL of N,N-dimethylformamide solvent and 5 g of the above-mentioned microporous polymer into a flask, ultrasonically vibrate for 60 min in an ultrasonic device, then add 12 g of nickel nitrate and 120 mL of water, continue ultrasonic vibration for 30 min, then stir for 24 h, control the stirring temperature to 40 ° C, filter, wash with water, and dry to obtain a microporous polymer coordinated with nickel ions.

[0036] Preparation of porous carbon loaded with nano-nickel: The microporous polymer coordinated with nickel ions was placed in a tubular furnace, nitrogen was introduced, the temperature was increased to 800°C at a heating rate of 3°C / min, and annealed for 2h to obtain porous carbon-loaded nano-nickel.

[0037] Example 3 Preparation of bisbenzotriazole bishydrazide compounds: 7 g of benzotriazole, 10 g of dimethyl 2,5-dibromoadipate, 0.6 g of polyethylene glycol 400, and 100 mL of a 0.35 g / mL potassium carbonate aqueous solution were added to a flask, and an ultrasonic-assisted reaction was carried out in an ultrasonic device for 2 h. The ultrasonic frequency was 20 KHz, and the reaction temperature was controlled at 70 °C. After the reaction, the mixture was cooled, water was added to precipitate, filtered, washed with water, and dried to obtain an intermediate.

[0038] Add 150 mL of methanol solvent, 15 g of the intermediate and 24 mL of hydrazine hydrate to a flask, stir and react for 10 h, control the reaction temperature to 30 ° C, and perform silica gel column chromatography after the reaction. The eluent is a solution with a volume ratio of ethyl acetate: n-hexane = 1:10 to obtain a bisbenzotriazole bishydrazide compound.

[0039] Preparation of microporous polymers containing catechol and benzotriazole structural units: Nitrogen was introduced into a three-necked flask, and 360 mL of N,N-dimethylformamide solvent, 6 g of 2,3-dihydroxyterephthalaldehyde, 16.2 g of bisbenzotriazole bishydrazide compound and 36 mL of glacial acetic acid were added. The reaction was stirred for 72 h, and the reaction temperature was controlled at 100 °C. After the reaction, the product was cooled, filtered, washed with ethanol, and dried to obtain a microporous polymer containing catechol and benzotriazole structural units.

[0040] Preparation of microporous polymer coordinated nickel ions: Add 300 mL of N,N-dimethylformamide solvent and 5 g of the above-mentioned microporous polymer into a flask, ultrasonically vibrate for 45 min in an ultrasonic device, then add 22 g of nickel nitrate and 200 mL of water, continue ultrasonic vibration for 45 min, then stir for 18 h, control the stirring temperature to 25 ° C, filter, wash with water, and dry to obtain a microporous polymer coordinated with nickel ions.

[0041] Preparation of porous carbon loaded with nano-nickel: The microporous polymer coordinated with nickel ions was placed in a tubular furnace, nitrogen was introduced, the temperature was increased to 900°C at a heating rate of 5°C / min, and annealed for 3 hours to obtain porous carbon-loaded nano-nickel.

[0042] Example 4 Preparation of bisbenzotriazole bishydrazide compounds: 9 g of benzotriazole, 10 g of dimethyl 2,5-dibromoadipate, 0.8 g of polyethylene glycol 400, and 150 mL of a 0.12 g / mL potassium carbonate aqueous solution were added to a flask, and an ultrasonic-assisted reaction was carried out in an ultrasonic device for 3 h. The ultrasonic frequency was 20 KHz, and the reaction temperature was controlled at 50 °C. After the reaction, the mixture was cooled, water was added to precipitate, filtered, washed with water, and dried to obtain an intermediate.

[0043] Add 200 mL of methanol solvent, 15 g of the intermediate and 24 mL of hydrazine hydrate to a flask, stir and react for 3 h, control the reaction temperature to 35 °C, and perform silica gel column chromatography after the reaction. The eluent is a solution with a volume ratio of ethyl acetate:n-hexane = 1:10 to obtain a bisbenzotriazole bishydrazide compound.

[0044] Preparation of microporous polymers containing catechol and benzotriazole structural units: Nitrogen was introduced into a three-necked flask, and 240 mL of N,N-dimethylformamide solvent, 6 g of 2,3-dihydroxyterephthalaldehyde, 13.2 g of bisbenzotriazole bishydrazide compound and 27 mL of glacial acetic acid were added. The reaction was stirred for 48 h, and the reaction temperature was controlled at 130°C. After the reaction, the reaction was cooled, filtered, washed with ethanol, and dried to obtain a microporous polymer containing catechol and benzotriazole structural units.

[0045] Preparation of microporous polymer coordinated nickel ions: Add 400 mL of N,N-dimethylformamide solvent and 5 g of the above-mentioned microporous polymer into a flask, ultrasonically vibrate for 60 min in an ultrasonic device, then add 30 g of nickel nitrate and 300 mL of water, continue ultrasonic vibration for 45 min, then stir for 18 h, control the stirring temperature to 40 ° C, filter, wash with water, and dry to obtain a microporous polymer coordinated with nickel ions.

[0046] Preparation of porous carbon loaded with nano-nickel: The microporous polymer coordinated with nickel ions was placed in a tubular furnace, nitrogen was introduced, the temperature was increased to 900°C at a heating rate of 5°C / min, and annealed for 2.5 hours to obtain porous carbon-loaded nano-nickel.

[0047] Comparative Example 1 The microporous polymer containing catechol and benzotriazole structural units prepared in Example 1 was placed in a tubular furnace, nitrogen was introduced, the temperature was increased to 800° C. at a heating rate of 2° C. / min, and annealed for 2 h to obtain porous carbon.

[0048] The electrochemical hydrogen evolution activity of porous carbon-supported nano-nickel was detected by a three-electrode system: the porous carbon-supported nano-nickel prepared in each embodiment, or the porous carbon prepared in Comparative Example 1, was mixed and ground evenly with polyvinylidene fluoride in a mass ratio of 1:9, an appropriate amount of N-methylpyrrolidone was added dropwise, and ultrasonic vibration was adjusted to a paste solution, and then the solution was coated on a nickel foam mesh and dried to prepare a hydrogen evolution working electrode. The reference electrode was a saturated calomel electrode, the counter electrode was a platinum electrode, and the electrolyte was a 1 mol / L potassium hydroxide solution. The electrocatalytic performance test was carried out in an electrochemical workstation. The scanning rate was 5 mV / s.

[0049] After electrochemical performance test, the instruction manual is attached Figure 3 and Figure 4 It is shown that the microporous polymer coordinated nickel ions as a hydrogen evolution catalyst can be used at a current density of 10 mA cm -2 When the overpotential of hydrogen evolution is -0.208 to -0.089 V, the Tafel slope is 69-98 mV / dec; in the comparative example, only porous carbon is used as a hydrogen evolution catalyst, and its electrochemical hydrogen evolution performance is not high, the overpotential of hydrogen evolution is -0.389 V, and the Tafel slope is 162 mV / dec Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing porous carbon-supported nano-nickel, characterized in that: Porous carbon-supported nano-nickel was prepared as follows: Step S1, introducing nitrogen into a three-necked flask, adding N,N-dimethylformamide solvent, 2,3-dihydroxyterephthalaldehyde, bisbenzotriazole dihydrazide compound and glacial acetic acid, cooling after reaction, filtering, washing and drying to obtain a microporous polymer containing catechol and benzotriazole structural units; Step S2, adding N,N-dimethylformamide solvent and the above-mentioned microporous polymer to a flask, ultrasonically vibrating in an ultrasonic device for 30-60 min, then adding nickel nitrate and water, continuing ultrasonic vibration for 30-60 min, and then stirring for 12-24 h, controlling the stirring temperature to 25-50° C., filtering, washing, and drying to obtain a microporous polymer coordinated with nickel ions; Step S3, the microporous polymer coordinated with nickel ions is placed in a tubular furnace, nitrogen is introduced, the temperature is increased to 700-900° C. at a heating rate of 2-5° C. / min, and annealed for 2-3 hours to obtain porous carbon-supported nano-nickel.

2. The method for preparing porous carbon-supported nano-nickel according to claim 1, characterized in that: In step S1, the ratio of N,N-dimethylformamide solvent, 2,3-dihydroxyterephthalaldehyde, bisbenzotriazole dihydrazide compound and glacial acetic acid is (40-60) mL:1 g:(2.2-2.7) g:(4.5-6) ​​mL.

3. The method for preparing porous carbon-supported nano-nickel according to claim 1, characterized in that: In step S1, the reaction temperature is controlled to be 100-130° C. and the reaction time is 48-96 h.

4. The method for preparing porous carbon-supported nano-nickel according to claim 1, characterized in that: In step S2, the ratio of N,N-dimethylformamide solvent, microporous polymer, nickel nitrate and water is (20-80) mL:1 g:(1-6) g:(15-60) mL.

5. The method for preparing porous carbon-supported nano-nickel according to claim 1, characterized in that: Step S1: The bisbenzotriazole bishydrazide compound is prepared according to the following method: Step S3, adding benzotriazole, dimethyl 2,5-dibromoadipate, polyethylene glycol 400, and potassium carbonate aqueous solution into a flask, performing ultrasound-assisted reaction in an ultrasound device, cooling after the reaction, precipitating, filtering, washing, and drying to obtain an intermediate; Step S4, adding methanol solvent, the intermediate and hydrazine hydrate into a flask, stirring and reacting for 3-10 h, controlling the reaction temperature to be 30-40° C., and performing silica gel column chromatography separation after the reaction to obtain a bisbenzotriazole bishydrazide compound.

6. The method for preparing porous carbon-supported nano-nickel according to claim 5, characterized in that: In step S3, the ratio of benzotriazole, dimethyl 2,5-dibromoadipate, polyethylene glycol 400, and potassium carbonate aqueous solution is (0.7-0.9) g:1 g:(0.05-0.08) g:(5-15) mL.

7. The method for preparing porous carbon-supported nano-nickel according to claim 6, characterized in that: The mass fraction of the potassium carbonate aqueous solution in step S3 is (0.12-0.6) g / mL.

8. The method for preparing porous carbon-supported nano-nickel according to claim 5, characterized in that: In step S3, the frequency of the ultrasound-assisted reaction is 20 KHz, the reaction temperature is controlled at 50-80°C, and the reaction time is 1-3 h.

9. The method for preparing porous carbon-supported nano-nickel according to claim 5, characterized in that: In step S4, the ratio of methanol solvent, intermediate and hydrazine hydrate is (10-20) mL:1 g:(1.6-3) mL.

Citation Information

Patent Citations

  • A ruthenium-nitrogen co-doped porous carbon catalyst, its preparation method, and its application in the electrochemical desorption of hydrogen.

    CN113136591B